Implementasi Sistem Monitoring Potensi, Ancaman, dan Demografi Desa Wisata Jatimulyo Berbasis Data Driven: Implementation of Data-Driven Monitoring System for Potential, Threats, and Demographics of Jatimulyo Tourism Village - Zakariyah, Muhammad; Sanjaya, Fadil Indra; Kalifia, Anna Dina; Ar-Razi Ab, Fariddudin; Hidayah, Taufik; Khoeri, Elfan Fanhas; Nurjaman, Muhammad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Village development and regional governance are central to Indonesia's national development agenda. However, in practice, monitoring demographic data, potential resources, and potential threats often transpires without the utilization of technology, yielding less accurate information. Furthermore, numerous villages, including Jatimulyo Tourism Village in Kulon Progo, have yet to fully embrace technology to harness the full potential of their local resources. Within this context, a pressing need exists for technological innovations to leverage the power of data in facilitating informed decision-making. The primary objective of this community engagement endeavor is to establish a data-driven village monitoring system to enhance the efficacy and efficiency of village monitoring processes while simultaneously promoting transparency, accountability, and community participation. The data-driven approach facilitates the collection of precise, automated data. Technology is anticipated to play a pivotal role in rectifying inaccuracies in information, offering crucial support to local government authorities and tourism managers in making well-informed decisions. This community service initiative's tangible outcome is creating a village monitoring system dashboard designed to facilitate decision-making processes and foster greater community involvement. Moreover, it is envisioned that this undertaking will maximize rural development and regional governance, instigate data-driven decision-making practices, foster the development of a robust village ecosystem, and ultimately enhance the overall well-being of the residents of Jatimulyo Tourism Village.